FAKTOR-FAKTOR YANG MEMPENGARUHI KEANDALAN DAN KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PT. PLN (PERSERO) KOTA BANDA ACEH - Irmawarti Irmawarti; Emmi Suryani; Eva Yulia (STIE DWI SAKTI BATURAJA, 2018)
The purpose of this study is to find out whether the quality of human resources, the use of information system technology and internal control together affect the reliability and timeliness of financial reporting at PT. PLN (Persero) Kota Banda Aceh. The population of this research is all employees at PT. PLN (Persero) Kota Banda Aceh which numbered 175 people. While the study sample was 64 employees. Based on the results of the research that has been done, that the Utilization of Information Technology and Internal Control affects the Reliability and Timeliness of Financial Reporting at PT. PLN (Persero) Banda Aceh. Constant value of 6.795, Manuasia Resource Capacity has a positive effect on Reliability and Timeliness of Financial Reporting of 0.782. Utilization of information technology has a positive effect on Reliability and Timeliness of Financial Reporting on PLN (Persero) Kota Banda Aceh, the effect is 0.420 units, Internal control has a positive effect on Reliability and Timeliness of Financial Reporting at PLN (Persero) Banda Aceh City of 0.673 units, Value correlation coefficient (R) of 0.792, the value of determination coefficient (R2) is 0.637.